2005
DOI: 10.1081/ada-200047934
|View full text |Cite
|
Sign up to set email alerts
|

Substance Involvement and the Trajectory of Criminal Offending in Young Males

Abstract: The current study investigated the influence of substance involvement on the trajectory of delinquency. Data were from 625 Buffalo, NY males aged 16-19, interviewed three times at 18-month intervals. Hierarchical linear models were fit separately for respondents with increasing and declining delinquency. In the increasing group, aIcohol involvment was associated with a higher starting point (intercept), and alcohol dependence and drug consequences were associated with a faster increase. In the declining group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 32 publications
(19 reference statements)
2
34
0
Order By: Relevance
“…Longitudinal surveys of adolescent males have found strong relationships between alcohol use, delinquency, and violent behavior (Moffitt, Caspi, Harrington, and Milne, 2002; Welte, Barnes, Hoffman, Wieczorek, and Zhang, 2005). Alcohol administration studies, which have focused on aggression toward someone of the same sex, have consistently demonstrated that moderate doses of alcohol increase men's aggressive behavior (for reviews see Chermack and Giancola, 1997; Ito, Miller, and Pollock, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal surveys of adolescent males have found strong relationships between alcohol use, delinquency, and violent behavior (Moffitt, Caspi, Harrington, and Milne, 2002; Welte, Barnes, Hoffman, Wieczorek, and Zhang, 2005). Alcohol administration studies, which have focused on aggression toward someone of the same sex, have consistently demonstrated that moderate doses of alcohol increase men's aggressive behavior (for reviews see Chermack and Giancola, 1997; Ito, Miller, and Pollock, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Informed consent was obtained from both respondents. Separate, face-to-face, structured interviews were conducted by trained interviewers at the Research Institute on Addictions (Welte, Barnes, Hoffman, Wieczorek, & Zhang, 2005). …”
Section: Methodsmentioning
confidence: 99%
“…In the initial wave 74% (n=625) of the households identified contained an eligible male who agreed to participate in the structured interview phase of the study (Welte et al, 2005). The racial composition of the original sample consisted of 49% white, 45% African American and 6% from other racial/ethnic backgrounds (Zhang, Wieczorek, & Welte, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Many parolees are returned to prison as a result of violating their conditions of parole because of substance abuse (Lynch & Sabol, 2001). Drug use also has been found to significantly impair young men's ability to mature out of delinquency (Welte, Barnes, Hoffman, Wieczorek, & Zhang, 2005; Zhang, Welte & Wieczorek, 2002). For example, among a sample of young delinquent men, alcohol dependence and negative consequences of drug use were found to be associated with a more rapid increase in criminal activity (Welte et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Drug use also has been found to significantly impair young men's ability to mature out of delinquency (Welte, Barnes, Hoffman, Wieczorek, & Zhang, 2005; Zhang, Welte & Wieczorek, 2002). For example, among a sample of young delinquent men, alcohol dependence and negative consequences of drug use were found to be associated with a more rapid increase in criminal activity (Welte et al, 2005). Moreover, studies involving drug treatment clients have demonstrated that reduced drug use is associated with reduced posttreatment criminal activities (Anglin & Perrochet, 1998; Farabee, Shen, Hser, Grella, & Anglin, 2001; Federal Bureau of Prisons, 1998; Fletcher, Tims, & Brown, 1997), further supporting the link between drug use severity and criminal conduct.…”
Section: Introductionmentioning
confidence: 99%